Transvaginal Ultrasound in Fertile Patients with Suspected Appendicitis: An Experience Report of Current Practice - Malek Tabbara; Nikolaos Evangelopoulos; Luigi Raio; Vanessa Banz; Heinz Zimmermann; Corinne Kim-Fuchs; Aristomenis K. Exadaktylos (Emergency Medicine International)
Background. Transvaginal ultrasound (TVU) in female patients with acute right lower quadrant (RLQ) abdominal pain is time and infrastructure intensive and not always available. This study aims to evaluate the role of TVU in these patients. Methods. Retrospective analysis identified 224 female patients with RLQ pain and TVU. Results. TVU revealed an underlying pathology in 34 (15%) patients, necessitating a diagnostic laparoscopy in 12 patients. Six patients (2%) had a true gynaecological emergency. The remaining 23 patients did not require surgery. The other 190 patients with RLQ pain had a bland TVU; 127 (67%) were discharged, while 63 patients (33%) received a diagnostic laparoscopy. Conclusion. The incidence of true gynaecological emergencies requiring urgent surgical intervention is very low in our patient cohort. TVU is a helpful tool if performed by a physician who is well trained in TVU.